2018
DOI: 10.1055/s-0038-1655757
|View full text |Cite
|
Sign up to set email alerts
|

Patch Angioplasty or Primary Closure Following Carotid Endarterectomy for Symptomatic Carotid Artery Stenosis

Abstract: Objectives  Guidelines recommend routine patching to prevent restenosis following carotid endarterectomy, mainly based on studies performed many years ago with different perioperative care and medical treatment compared with current standards. Aim of the present study was to compare primary closure (PRC) versus patch closure (PAC) in a contemporary cohort of patients. Methods  Consecutive patients treated by carotid endarterectomy for symptomatic stenosis between January 2006 and April 2016 were retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 16 publications
(24 reference statements)
1
16
0
2
Order By: Relevance
“…[11,12] Therefore, the patchplasty is now considered to be the standard of practice for the patients undergoing conventional CEA. Although a previous meta-analysis revealed that the patch angioplasty was associated with lower restenosis and perioperative stroke rates, [13] a recent retrospective study performed by Huizing E et al [14] questioned this assumption. These authors suggested that, in patients with symptomatic CAS, there was no difference in PA and PC groups in terms of restenosis, stroke, or death rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11,12] Therefore, the patchplasty is now considered to be the standard of practice for the patients undergoing conventional CEA. Although a previous meta-analysis revealed that the patch angioplasty was associated with lower restenosis and perioperative stroke rates, [13] a recent retrospective study performed by Huizing E et al [14] questioned this assumption. These authors suggested that, in patients with symptomatic CAS, there was no difference in PA and PC groups in terms of restenosis, stroke, or death rates.…”
Section: Discussionmentioning
confidence: 99%
“…These authors suggested that, in patients with symptomatic CAS, there was no difference in PA and PC groups in terms of restenosis, stroke, or death rates. [14] After this study, Huizing E et al [14] performed a meta-analysis based on moderate-quality trial data, and they found that perioperative stroke and restenosis rates were lower in the patients undergoing PA when compared to those undergoing PC. [15] The meta-analysis of Huizing E et al [14] confirmed the results of previous meta-analyses, in which the PA was deemed safer when compared to the PC technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Также в исследовании с ретроспективным анализом результатов КЭА у 1737 пациентов, одной половине которых была осуществлена ангиопластика заплатой, а другой -первичным швом, не было обнаружено достоверных отличий по осложнениям в ранний и поздний послеоперационные периоды в зависимости от способа закрытия разреза [7]. Кроме того, Huizing и соавторы отмечали большую частоту рестенозов через 6 недель имплантации у пациентов с заплатой (6%) по сравнению с группой, в которой использовали первичное ушивание (3%) [8]. Похожую картину наблюдали и через год после операции с количеством случаев рестеноза в анализируемых группах 31,6% и 14,1% соответственно [8].…”
Section: Introductionunclassified
“…Кроме того, Huizing и соавторы отмечали большую частоту рестенозов через 6 недель имплантации у пациентов с заплатой (6%) по сравнению с группой, в которой использовали первичное ушивание (3%) [8]. Похожую картину наблюдали и через год после операции с количеством случаев рестеноза в анализируемых группах 31,6% и 14,1% соответственно [8].…”
Section: Introductionunclassified